2002
DOI: 10.1021/ma012207y
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Ring-Opening Polymerization of 6-, 7-, 9-, 12-, 13-, 16-, and 17-Membered Lactones. Comparison of Chemical and Enzymatic Polymerizations

Abstract: The kinetics of bulk polymerization of 6-, 7-, 9-, 12-, 13-, 16-, and 17-membered lactones initiated with a zinc 2-ethylhexanoate/butyl alcohol system at 100 °C was studied and compared with that of lipase-catalyzed polymerization. Instantaneous concentrations of the lactone monomers were determined on the basis of the relative intensities of signals in the 1H NMR spectra (500 MHz, CDCl3 as a solvent, room temperature) from the ω-methylene protons (−(CH2) x - 1CH 2 OC(O)−) (where x = 4, 5, 7, 10, 11, 14, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
146
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(151 citation statements)
references
References 42 publications
3
146
0
Order By: Relevance
“…[39, 40,[83][84][85] There is a tendency that, with lipase PF, larger ring-sizes have larger polymerization rates, with one order-of-magnitude differences typically seen (Table 2); that is, the higher polymerizability of the macrolides was explained by the higher rate in the formation of EM. Values of the Michaelis-Menten constant [83] These results suggest that the reaction rate is mainly governed by the larger value of V max , and much less by the binding ability.…”
Section: Terminator Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[39, 40,[83][84][85] There is a tendency that, with lipase PF, larger ring-sizes have larger polymerization rates, with one order-of-magnitude differences typically seen (Table 2); that is, the higher polymerizability of the macrolides was explained by the higher rate in the formation of EM. Values of the Michaelis-Menten constant [83] These results suggest that the reaction rate is mainly governed by the larger value of V max , and much less by the binding ability.…”
Section: Terminator Methodsmentioning
confidence: 99%
“…During the propagation reaction, ring-strain of lactone monomer is operative for the rate of ROP. [84] Today, lipase CA (Novozyme 435) is widely used; its structure was determined by X-ray crystallographic analysis.…”
Section: Terminator Methodsmentioning
confidence: 99%
“…1 Metal complexes are the most commonly explored catalysts; they include tin, 2,3 aluminum, [4][5][6][7] iron, 8,9 scandium, [10][11][12] yittrium, 13,14 zinc, 15,16 bismuth, 17 ruthenium, 18 zirconocene, 19 and so on. A popular polymerization system for PCL is ring-opening polymerization (ROP) of ecaprolactone catalyzed by organotin compound.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of unsubstituted lactones with ring size larger than six, the rate constant of the medium-size lactones in the chemical polymerization catalyzed by zinc octanoate was much larger than that of the macrolides, since the macrolides have much lower ring strain, and hence, show less polymerizability. 4 In this study, the anionic polymerizability of lactones using sodium methoxide as initiator has been compared with that by the lipase catalyst. In all cases examined, the polyesters with molecular weight of several thousands were obtained and the polymerizability of α-and ω-substituted lactones was lower than that of unsubstituted ones (Figure 3).…”
Section: Comparison Of Chemical and Enzymatic Polymerizability Of Submentioning
confidence: 99%
“…Our recent report showed that macrolides possessed much lower reactivity in the polymerization catalyzed by zinc octanoate than δ-valerolactone (1a) or ε-caprolactone (2a). 4 In the Pseudomonas fluorescens lipase-catalyzed polymerization, on the other hand, the reverse tendency was observed. 5 This is due to the stronger recognition of the macrolides by lipase catalyst.…”
Section: Introductionmentioning
confidence: 99%